2019
DOI: 10.1021/acs.jcim.8b00850
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism Regarding Allosteric Modulation of Ligand Binding and the Impact of Mutations on Dimerization for CCR5 Homodimer

Abstract: In this work, we combined accelerated molecular dynamics (aMD) and conventional molecular dynamics (cMD) simulations coupled with the potential of mean force (PMF), correlation analysis, principal component analysis (PCA), and protein structure network (PSN) to study the effects of dimerization and the mutations of I52V and V150A on the CCR5 homodimer, in order to elucidate the mechanism regarding cooperativity of the ligand binding between two protomers and to address the controversy about the mutation-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 89 publications
2
25
0
Order By: Relevance
“…66 Moreover, the computational study together with the site-direct muta-genesis study performed by Zhang et al revealed that the CCR5 homodimerization involved TM1, TM2, TM3, and TM4. 67 In the present study, considering the fact that the attachment point for the spacer of the bivalent ligands designed, that is, the 3′-methyl group on the 1,2,4-triazol moiety of maraviroc pointed toward TM1, TM2, and TM3, and the possible steric hindrance of extracellular loop 1 (ECL1) between TM2 and TM3, TM1/TM2 was therefore selected as the plausible dimer interface of the CCR5. An MOR-CCR5 heterodimer model in which TM5/6 of the MOR and TM1/2 of the CCR5 were selected as dimer interfaces in complexing with VZMC013 (Figure S6a) was inserted into a membrane-aqueous sodium chloride solution system (Figure S6b) and subjected to further MD simulations.…”
Section: ■ Results and Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…66 Moreover, the computational study together with the site-direct muta-genesis study performed by Zhang et al revealed that the CCR5 homodimerization involved TM1, TM2, TM3, and TM4. 67 In the present study, considering the fact that the attachment point for the spacer of the bivalent ligands designed, that is, the 3′-methyl group on the 1,2,4-triazol moiety of maraviroc pointed toward TM1, TM2, and TM3, and the possible steric hindrance of extracellular loop 1 (ECL1) between TM2 and TM3, TM1/TM2 was therefore selected as the plausible dimer interface of the CCR5. An MOR-CCR5 heterodimer model in which TM5/6 of the MOR and TM1/2 of the CCR5 were selected as dimer interfaces in complexing with VZMC013 (Figure S6a) was inserted into a membrane-aqueous sodium chloride solution system (Figure S6b) and subjected to further MD simulations.…”
Section: ■ Results and Discussionsupporting
confidence: 63%
“…Thus, they speculated that other interfaces have a higher possibility to be the interface of the CCR5 . Moreover, the computational study together with the site-direct mutagenesis study performed by Zhang et al revealed that the CCR5 homodimerization involved TM1, TM2, TM3, and TM4 . In the present study, considering the fact that the attachment point for the spacer of the bivalent ligands designed, that is, the 3′-methyl group on the 1,2,4-triazol moiety of maraviroc pointed toward TM1, TM2, and TM3, and the possible steric hindrance of extracellular loop 1 (ECL1) between TM2 and TM3, TM1/TM2 was therefore selected as the plausible dimer interface of the CCR5.…”
Section: Resultssupporting
confidence: 59%
“…The observation is consistent with and demonstrates previous work showing that GPCR dimers may exert allosteric effects on binding with ligands. 26,27 Another interesting work using molecular dynamics simulation 28 found that the binding pocket volume of the CCR5 monomer is 567 Å3. Upon dimerization, the pocket volume of the first subunit increases to 650 Å 3 , while that of the second subunit reduces to 412 Å 3 .…”
mentioning
confidence: 99%
“…45 The contribution of van der Waals (vdW) free energy is stronger in the dimer bound by the glutamates than in the apo system, indicating that the main driving force for the dimerization is vdW interaction, similar to the class A GPCR dimers reported. 38 2.1.2. Important Interface Residues Contributing to the Dimerization.…”
Section: Resultsmentioning
confidence: 99%